ANALISIS & PERANCANGAN SISTEM INFORMASI AKUNTANSI PADA KOPERASI MAHASISWA UNY - Diah Novitaningrum (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The aim of this research is to analyze, design and create an effective and efficient accounting information system at the Yogyakarta State University (UNY) Student Cooperative. The method used to obtain data is direct observation and in-depth interviews with cooperative administrators, as well as documentation studies related to the current accounting system. The research results show that the system designed is successful in meeting the needs of cooperatives by providing convenience in financial recording and reporting, as well as increasing transparency and accountability. Thus, the implementation of the new accounting information system in the UNY Student Cooperative can be the most effective model in managing the finances of student cooperatives in other educational institutions.